2013
DOI: 10.1371/journal.pone.0083041
|View full text |Cite
|
Sign up to set email alerts
|

Reference Genes Selection for Quantitative Real-Time PCR Using RankAggreg Method in Different Tissues of Capra hircus

Abstract: Identification of reference genes with stable levels of gene expression is an important prerequisite for obtaining reliable results in analysis of gene expression data using quantitative real time PCR (RT-qPCR). Since the underlying assumption of reference genes is that expressed at the exact same level in all sample types, in this study, we evaluated the expression stability of nine most commonly used endogenous controls (GAPDH, ACTB, 18S rRNA, RPS18, HSP-90, ALAS, HMBS, ACAC, and B2M) in four different tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
5
31
0
Order By: Relevance
“…The most stable genes were Ap47, PP2A and S23 in branchlets; S23, GAPDH and PP2A in roots; and S23, Ap47 and PP2A in nodules (Online Resource 6). Altogether, these results are in agreement with recent studies, where it was reported that the expression of reference genes may vary with the experimental conditions as well as with cell/tissue type (Kozera and Rapacz 2013;Mehta et al 2010;Ling and Salvaterra 2011;Najafpanah et al 2013). On the other hand, the results support the findings of Klie and Debener (2011), that a new generation of reference genes will replace classical reference genes such as Ubi and Tub.…”
Section: Inter-tissue Analysissupporting
confidence: 93%
“…The most stable genes were Ap47, PP2A and S23 in branchlets; S23, GAPDH and PP2A in roots; and S23, Ap47 and PP2A in nodules (Online Resource 6). Altogether, these results are in agreement with recent studies, where it was reported that the expression of reference genes may vary with the experimental conditions as well as with cell/tissue type (Kozera and Rapacz 2013;Mehta et al 2010;Ling and Salvaterra 2011;Najafpanah et al 2013). On the other hand, the results support the findings of Klie and Debener (2011), that a new generation of reference genes will replace classical reference genes such as Ubi and Tub.…”
Section: Inter-tissue Analysissupporting
confidence: 93%
“…Given the differences observed in our comparison, we conclude that normalization against a single “commonly used reference gene” may lead to serious discrepancies in data interpretation. GAPDH was found to be unsuitable for normalization in skeletal muscle development in pig [ 48 ]; similar results were reported in goat [ 16 ] and cattle [ 51 ]. In addition, GAPDH was observed to be up-regulated and down-regulated under various conditions [ 7 , 9 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 58%
“…More recently, Najafpanah MJ et.al. [ 16 ] carried out an analysis of nine candidate reference genes in goat; HSP-90 was almost always the most stable reference gene in longissimus muscle, liver and visceral and subcutaneous fat.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that pcna, gapdh, 18S rRNA, hsp90 , and rbcl have been selected as potential reference genes for determining gene expression in different tissues from various species, including plants1531, goat32, and fish33. In the present study, the three algorithms provided slightly different stability rankings, which was not unexpected because these algorithms use different approaches.…”
Section: Discussionmentioning
confidence: 50%